Features of changes in laboratory parameters of patients against the use of dexmedetomidine in septoplasty. - A. A. Ayvardgi (Medičnì Perspektivi)
Currently, a lot of attention of scientists all over the world is paid to the perioperative management strategy, taking into account the volume of surgical intervention, the presence of comorbidities and their possible complications. This makes it possible to reduce mortality, decrease the number of adverse events in the intra- and postoperative period, effectively cope with pain, advance recovery and rehabilitation, and also increase patients’ satisfaction with the quality of medical care. We studied indices of 58 adult patients who underwent septoplasty. Patients were divided into 2 groups. In group “D”, dexmedetomidine was infused, which began 10 minutes before the induction of anesthesia at a dose of 0.7 μg/kg/h and ended 10 minutes before the end of the surgical intervention. The clinical blood test (hemoglobin level, erythrocytes, leukocytes, rods count), body temperature of patients, coagulogram (INR, fibrinogen level, Dyuk bleeding time) were studied. When comparing the indicators of clinical analysis in the postoperative period in the control group leukocytosis and stab left shift (p <0.001) was observed. For patients undergoing dexmedetomidine infusion, leukocyte and bacillus levels were normal. In both postoperative follow-up groups, low-grade fever was detected (p <0.001). In the control group, 12 hours after surgery, body temperature rose to febrile values. During the operative intervention, the “D” group was characterized by the better indices of blood coagulation. In the group "K" on the second day of the postoperative period, there was a slight increase in coagulation. The level of intraoperative blood loss in the “D” group was significantly lower than in the control group (p<0.001). In the “D” group in the postoperative period, the minimum decrease in hemoglobin was determined in contrast to the control group (p<0.001). The use of dexmedetomidine infusion leads to a decrease in the manifestations of a systemic inflammatory response in surgical interventions for the curvature of the nasal septum. The introduction of dexmedetomidine provides better blood coagulation during septoplasty. Infusion of dexmedetomidine causes a decrease in blood loss and consequently the maintenance of hemoglobin concentration at the proper level.